Atmospheric‐Pressure Synthesis of 2D Nitrogen‐Rich Tungsten Nitride - Yu, Huimin; Yang, Xin; Xiao, Xu; Chen, Ming; Zhang, Qinghua; Huang, Liang; Wu, Jiabing; Li, Tianqi; Chen, Shuangming; Song, Li; Gu, Lin; Xia, Bao Yu; et al. (Advanced materials (Weinheim), 2018)
2D transition metal nitrides, especially nitrogen‐rich tungsten nitrides (WxNy, y > x), such as W3N4 and W2N3, have a great potential for the hydrogen evolution reaction (HER) since the catalytic activity is largely enhanced by the abundant WN bonding. However, the rational synthesis of 2D nitrogen‐rich tungsten nitrides is challenging due to the large formation energy of WN bonding. Herein, ultrathin 2D hexagonal‐W2N3 (h‐W2N3) flakes are synthesized at atmospheric pressure via a salt‐templated method. The formation energy of h‐W2N3 can be dramatically decreased owing to the strong interaction and domain matching epitaxy between KCl and h‐W2N3. 2D h‐W2N3 demonstrates an excellent catalytic activity for cathodic HER with an onset potential of −30.8 mV as well as an overpotential of −98.2 mV for 10 mA cm−2. Ultrathin 2D hexagonal‐W2N3 (h‐W2N3) flakes are synthesized at atmospheric pressure via a salt‐templated method. The formation energy of h‐W2N3 can be dramatically decreased owing to the strong interaction and domain matching epitaxy between KCl and h‐W2N3. 2D h‐W2N3 demonstrates an excellent catalytic activity for the cathodic hydrogen evolution reaction.